Plastic Surgeons at the Forefront: Evaluating Plastic Surgery Interventions for Earthquake Victims - Galip Gencay Üstün; Nur Erek; Süleyman Yildizdal; Murat Kara; Gökhan Sert; Fatma Figen Özgür (Turkish Journal of Plastic Surgery)
Introduction: Earthquakes are a formidable reality in Turkey. Most recently, on February 6th, 2023, two earthquakes with 7.7 and 7.6 magnitudes struck, affecting around 14 million people, making it the most catastrophic earthquake in the country’s history regarding damage and life loss. Following the first aid on-site, many patients needed a referral to larger centers for further interventions. Patients and Methods: This retrospective study presents the treatment approach of the plastic surgery department of a tertiary referral center to the victims of the aforementioned earthquakes. Patients were evaluated every 3 days: debridement, wound edge approximation with rubber bands, and vacuum-assisted closure (VAC) dressing were performed under operating room conditions. Primary closure was performed when possible; otherwise, partial-thickness skin grafts and regional/free flaps were utilized. Results: Of 127 patients (68 women, 59 men; 2–78 years), 91 underwent at least one surgical operation, while 36 were managed with bedside procedures. A total of 609 surgical procedures were performed. Tissue defects of 58 patients were approximated with rubber bands and VAC dressings. Forty-two patients required skin grafting, and 12 patients had regional/free flap surgery. Flap loss occurred in two patients. The average duration of stay under rubble was 23.5 h (max 120 h). Conclusion: Minimizing tissue loss and preserving functionality are key principles in the management of earthquake survivors. Excessive workload in a disaster setting can be managed by following the reconstruction ladder. Despite the efforts, earthquake survivors may experience cosmetic, functional, and psychological losses, causing a considerable burden on plastic surgery clinics and the general healthcare system in Turkey.